A child, homozygous for a stop codon in exon 11, shows milder cystic fibrosis symptoms than her heterozygous nephew. Issue 11 (November 1990) - Cuppens, H; Marynen, P; Berghe, H Van den; Cassiman, J J; Boeck, C De; Eggermont, E; Baets, F De
Abstract : The clinical and molecular findings in an infant with mild manifestations of cystic fibrosis, who is homozygous for the G542X mutation, and her heterozygous nephew, who is severely affected, are described.